2020
DOI: 10.1136/ijgc-2020-001315
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality adjuvant therapy and survival outcomes in stage I–IV uterine carcinosarcoma

Abstract: ObjectivesUterine carcinosarcoma is a rare, aggressive form of uterine cancer with a high recurrence rate and poor survival at all stages. We sought to evaluate the outcomes of patients treated with chemotherapy versus a combination of chemotherapy and radiation (chemoradiation) to determine survival.MethodsA multicenter retrospective analysis of patients with stage I–IV carcinosarcoma was conducted from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…We observed an increase in retroperitoneal recurrence in patients receiving adjuvant chemotherapy alone versus chemoradiation. These findings agree with existing retrospective as well as prospective data, suggesting the importance of radiation therapy in retroperitoneal disease control [13,[20][21][22]. Additionally, we observed a higher incidence of isolated positive para-aortic lymph nodes (18.1%) than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…We observed an increase in retroperitoneal recurrence in patients receiving adjuvant chemotherapy alone versus chemoradiation. These findings agree with existing retrospective as well as prospective data, suggesting the importance of radiation therapy in retroperitoneal disease control [13,[20][21][22]. Additionally, we observed a higher incidence of isolated positive para-aortic lymph nodes (18.1%) than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…49 Finally, the authors found that the "sandwich as chemotherapy-radiotherapy-chemotherapy" schedule provided a best benefit to patients with UCS because this "sandwich" therapy was associated with longer OS than sequential chemotherapyradiotherapy and radiotherapy-chemotherapy protocols (34 vs 14 months, p = 0.038). 49 In the current study, our results failed to show the positive impact on prognosis with adding radiotherapy, although many studies, including a recent Taiwan's largest study, favored its additional or synergistic positive effect on survival of UCS. [47][48][49][50] To further dissect the potential reason, we analyzed a total of six patients (five in PP and one in IP) who had been treated with radiotherapy as adjuvant therapy.…”
Section: Adjuvant Therapymentioning
confidence: 98%
“…During a median follow-up of 60 months, the authors found the best outcomes (PFS = 35 months, 95 % CI, 0.26-0.43; OS = 47 months, 95 % CI, 0.38-0.56) in women treated with IP. 49 However, recent evidence supports that UCS is various forms of poorly differentiated uterine carcinomas, 1,2,13,17,[29][30][31][32] contributing to the reconsideration of the use of paclitaxel in place of ifosfamide for UCS. 35,36 Powell et al 35 conducted a single-arm phase II GOG-232B trial to evaluate the efficacy of PP for recurrent or metastatic UCS to obtain 13% and 41%, of compete and partial response rates, respectively, in 55 advanced UCS (stage III and IV) patients.…”
Section: Chemotherapy Regimenmentioning
confidence: 99%
“…Besides, like endometrial adenocarcinoma, the uterine carcinosarcoma risk is decreased by the history of oral contraceptive pill use 6 . However, uterine carcinosarcoma presents with extra‐uterine disease in 60% of cases, while most of the endometrial ademocarcinoma is of early stage and low grade 7–9 . The 5‐year survival of uterine carcinosarcoma is estimated to be less than 40%, and more than half will recur although primary surgery and adjuvant therapy 8,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, uterine carcinosarcoma presents with extra‐uterine disease in 60% of cases, while most of the endometrial ademocarcinoma is of early stage and low grade 7–9 . The 5‐year survival of uterine carcinosarcoma is estimated to be less than 40%, and more than half will recur although primary surgery and adjuvant therapy 8,10 . Tumor stage was identified to be the most important prognostic factor for uterine carcinosarcoma 11 …”
Section: Introductionmentioning
confidence: 99%